Loyalty or Inertia? Customer Perspective on Traditional Micro-Retailing of Fisheries Commodities in Small Islands Coastal Area - Rahantoknam, Meyske A.; Teniwut, Wellem A.; Ngabalin, Anna M. (International Review of Management and Marketing, 2017)
The traditional micro-retailing market its existence today threatened by the strong penetration of supermarkets, the condition does not occur only in big cities in developed country but also in development country such as rural coastal area. In order to measure the sustainability and durability on existence of the traditional wet market against rapid penetration of supermarket then study to investigate whether the customer who shop wet product on traditional market categories as loyal or inertia (spurious loyalty) is necessary. This research conducted in the Kei Islands which is rural coastal area in Indonesia with respondents were customers who shop wet product on the traditional micro-retail market for at least four times in a month. Using the structural equation modeling, the results of this research showed that customer who buy fisheries wet product on the traditional micro-retail market in Kei Islands were identified as spurious loyalty or inertia. Implication of this result for local governments need to tightening regulation to prevent supermarket penetration especially in rural area and for seller (fishermen and aquaculture farmers) to increase their brand image by maintaining the consistency of quantity and quality of their product to keep their current customers against penetration of supermarket. Keywords: Traditional micro-retailing market, fisheries commodity, rural coastal areas. JEL Classification: M31